Kemampuan Menspesifikasi Topik Sebagai Bentuk Perwujudan Keterampilan Menulis Esai - Tresiana Sari Diah Utami; Katarina Retno Triwidayati; Maria Angelina Priyanti (Universitas Negeri Makassar, 2020)
Essay writing has the characteristic of focusing the discussion on one thing. The focus of the problem chosen is discussed widely and thoroughly. This research is a qualitative study conducted in the 2018/2019 academic year and funded by the Ministry of Research and Technology with the Beginner Lecturer Research scheme in 2019. The research was conducted at Musi Charitas Catholic University with a population of 382 writings and a sample of 180 random samples. The study was conducted with pen and paper based text, which provides writing texts to students studied. The students studied were asked to read the predetermined news text, analyze the topics contained in the news, then write a simple essay text based on the results of the analysis. The student's writing is then assessed by two people and the final grade is determined by calculating the average of the scores of the two assessors. This paper discusses the ability of students in writing specified on the character of the essay which is a reaction or statement of one's views on the topic discussed. Therefore, the expected text only focuses on one topic from a number of topics presented in the main text (news). The results showed 79.4% of students studied were not able to write essays that had one single topic. Students still explain the topics contained in the first text and do not strengthen their argument with evidence, but only explain the topics in the first text. There are only 12.2% of students who are able to write essay texts that describe one topic and complete it with supporting arguments and evidence.